Ownership And Control Of The Hungarian Press - James, Beverly; Gálik, Mihály (Javnost-The Public, 1999)
This article analyses the economic structure of the Hungarian press. We describe the circulation figures of national, political daily newspapers, their editorial profiles and market positions, how they were privatised, and how their editorial content is controlled. We also look at the ownership and control of the regional and weekly press. The analysis reveals that despite the unprofitability of most national newspapers, the market is relatively stable. While control of editorial content is mainly a function of ownership and market forces, journalists at some publications have secured a degree of independence. East Central European nations have widely embraced liberal-pluralist economic and political models. Here, press freedom is equated with private ownership by individuals, and the market is seen as the surest safeguard against state interference. But in practice, the press throughout the region is still heavily saturated with politics. Thus, our economic analysis is followed by a case study that examines recent efforts by the Hungarian government to use public money to establish a right- centrist newspaper. The discourse surrounding that event is used to explore notions of cultural democracy where the active participation of journalists and citizens in the production of a news reading culture is central.